Revivalist Translation in Contemporary Arabic Architecture - AL Dahwi, Suha Hassan; Sameen, Marwa Munther (Iraqi Journal of Architecture and Planning, 2018)
Translation lead in general a prominent role to transfer different sciences , knowledge and cultures, particularly in keeping up with scientific and literary developments. Because of the importance of translation and its relationship to architecture led to the identification of general axis of the research, which represents the â€œEmployment translation in architectureâ€. The research discussed the previous Architectural Studies that related to concept of translation and show that there was a difference in dealing with the translation of various movements in architecture, and the appearance of several employments can be identified with differences, pluralism, revivalism, interpretation, paradox, then the research problem identified by ((lack of objective holistic vision reveals privacy revivalist translation in contemporary Arab architecture)), and the objective of this research was represented by ((the formation of a theoretical, objective, comprehensive framework for the properties of the revivalist translation and using them to discover the application privacy of the concept in Arab contemporary architecture)) .Research reached conclusions and recommendations.